2017
DOI: 10.3389/fonc.2017.00200
|View full text |Cite
|
Sign up to set email alerts
|

Long-term Treatment Response and Patient Outcomes for Vestibular Schwannoma Patients Treated with Hypofractionated Stereotactic Radiotherapy

Abstract: PurposeThe aim of this study is to evaluate long-term treatment outcome and toxicities among vestibular schwannoma (VS) patients treated with hypofractionated stereotactic radiotherapy (HSRT).Methods383 patients with unilateral VS treated with HSRT (25 Gy, five fractions) between 1995 and 2007 were retrospectively reviewed. Treatment failure was defined as requiring salvage microsurgery. Posttreatment new/progressive clinical symptoms or increases in baseline tumor volume (BTV) due to treatment effect or progr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In the current study, the median time to progression was 42 months without any treatment failure after 8 years. This is consistent with the results of long‐term studies that showed that late treatment failure is uncommon after SRS/SRT 18,29 …”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the current study, the median time to progression was 42 months without any treatment failure after 8 years. This is consistent with the results of long‐term studies that showed that late treatment failure is uncommon after SRS/SRT 18,29 …”
Section: Discussionsupporting
confidence: 90%
“…This is consistent with the results of long-term studies that showed that late treatment failure is uncommon after SRS/SRT. 18,29 In the current study, Koos grade III/IV was the only factor associated with disease progression. Koos grade III is defined as extrameatal tumors in contact with the brainstem, whereas Koos grade IV is an extrameatal tumor that compresses the brainstem.…”
Section: Discussionmentioning
confidence: 48%
“…Finally, at a median follow-up of 4 years, hearing loss tended to plateau at 1 year, earlier than other long-term series. [42][43][44] Proton therapy may have a greater biological effect on normal tissues, which could contribute to greater hearing loss earlier than anticipated.…”
Section: Discussionmentioning
confidence: 99%
“…The outcome reflected similar favourable rates of control (80%-90%) in vestibular schwannoma treated with hypofractionated radiotherapy. 8,9 Third, our case suggests that control of inflammation within an oculomotor nerve schwannoma may be more important than reduction of tumour size. Finally, our case highlights that inaccurate medical terminology can have adverse and long-term affects on patient care.…”
mentioning
confidence: 80%